TINGKAT ADOPSI TEKNOLOGI DALAM PENGENDALIAN HAMA TERPADU DENGAN MENGGUNAKAN TANAMAN REFUGIA PADA BUDIDAYA PADI DI KECAMATAN CIANJUR KABUPATEN CIANJUR - Farihat Zaki Prakoso; Dedy Kusnadi; Harniati Harniati (Sekolah Tinggi Pariwisata Mataram, 2020)
Cianjur District is one area that has the potential to produce rice, especially in the lowlands because it has a large area of ​​rice harvest area in Cianjur Regency. Based on BPS data for 2018, Cianjur District has an area of ​​rice harvesting area of ​​2,501 Ha. According to the Programa Subdistrict of Cianjur in 2018, farmers who had applied the IPM concept were 81%. The data shows that more than half of the farmers in Cianjur District have applied the IPM concept. The research aims to describe the level of technology adoption in integrated pest control using refugia plants, analyze factors related to the rate of technology adoption, and formulate strategies to increase technology adoption in integrated pest control by using refugia plants in rice cultivation. The study was conducted in Cianjur Subdistrict Cianjur Regency in March to July 2020. The research sample was 41 rice farmers taken using purposive sampling technique. The data analysis technique used is descriptive analysis, multiple linear regression analysis, and a strategy model for developing farmers' adoption rates. The results showed that the level of technology adoption in integrated pest control using refugia plants in rice cultivation in Cianjur District was included in the medium category with a percentage (80 , 5%), so it needs to be increased again. Factors that influence the level of technology adoption in integrated pest control using refugia plants in rice cultivation are length of time and relative profit. The strategy to increase the level of technology adoption in the use of refugia plants as integrated pest control is to strengthen extension activities by increasing extension intensity, extension methods through demonstration methods and demonstration plots, and extension materials and media that are more suited to farmers' needs.